The cloning and chcracterization of mycobacterium tuberculosis katG gene - Martin, Eugene Ray (2005)
Tuberculosis is a disease that bas long plagued man for many centuries. The earliest known name of this disease is Phthisis ("to waste") by the Greeks. It has also been known as consumption in the 1800s, wasting disease, and the white plague. This disease is known as the leading cause of death from a single infectious agent, with ·a prevalence of greater than 1.6 billion people (Whitney and Wainberg, 2002). Until the mid-1800s, people thought that tuberculosis, or TB, was bereditaJy~ ln 1865 a .french surgeon, Jean-Antoine Villemin, proved that TB was contagiou~ and . in.lS82 .a German-scientist named Robert. Koch .discov.ered.thebacterimn .. that etuses TB, Mycobacterium tuherculo!;;is. TB is caused by an organism called Mycobacterium tuberculosis (MTB) also sometimes called as the tubercle baciJii. ·It is a member of the genus mycobacteriwn which consists of members of the MiB. complex and more than 80 $J1eeies of nontubercular mycobacteria inciuding pathogenic, opportunistic and non pathogenic species (Soini et al., 2001 ). Mycobacteria can cause a variety of diseases. Sotne mycobacteria are called tuberculous mycobacteria because they cause TB or diseases similar to TB. These mycobacteria are MTB, M bovis, and M. africanunl. Other mycobacteria are called non-tuberculous mycobacteria because they do not cause TB. One common type of nontuberculous mycobacteria is M avium complex. Non-tuberculous mycobacteria are not usually spread from person to person. Tuberculosis (TB) is a commooicable chronic granulomatous disease caused by MrB. It usually involves the lungs but may effect any other organ or tissue in thebody (Kumar, et a/.,2003). Tuberculosis is normally spread through airborne traitsmission of droplet nuclei containing the MTB bacili A majority of cases involves the lungs and is known as pulmonary tuberculosis wbere as extra pulmonary tuberculosis is due to the infection of other parts of the human body. About 80-90% of tuberculosis involves pulmonary tuberculosis and 10-20% involves extra pulmonmy tuberculosis.